The Influence of Physical Evidence, Price and Word Of Mouth on the Decision to Purchase Camphor Wood at UD. Source: Rizki - Fitri Handayani; Ike Susanti; M.Chusnul Khitam; Yunni Rusmawati dj (RTTM, 2024)
This research is to determine the influence of physical evidence, price and word of mouth on purchase decisions. The research method used was quantitative descriptive using analytical test tools, namely the determination coefficient test, multiple linear regression test, t-test and F test. From the results of data processing, the value of t calculation for physical evidence (X1) was calculated (2,470) ˃ttable (1,996) with a significance value of 0.016 < 0.005, the price (X2) was tcalculated (4,916) ˃ table (1,996) with a significance value of 0.000 < 0.005, word of mouth (X3) was calculated (2,119) ˃ table (1,996) with a significance value of 0.038 < 0.005, This means that physical evidence, price and word of mouth have a partial and significant effect on purchase decisions. From the F test, the F value was calculated as Fcalculated 49.478 ˃ Ftable 2.74 with a significant level of 0.000 < 0.05, which means that physical evidence, price and word of mouth have a simultaneous and significant effect on the purchase decision. Meanwhile, the result of multiple linear regression obtained the equation Y = 4.203 + 0.370 X1 + 0.484 X2 + 0.303 X3. Based on this study, it can be concluded that physical evidence, price and word of mouth have an influence on purchase decisions partially and simultaneously and it can be seen that price is the most dominant variable influencing consumer purchase decisions in UD. Source: Rizki.